The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.exer.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Optical treatment strategies to slow myopia progression: Effects of the visual extent of the optical treatment zone

Abstract: In order to develop effective optical treatment strategies for myopia, it is important to understand how visual experience influences refractive development. Beginning with the discovery of the phenomenon of form deprivation myopia, research involving many animal species has demonstrated that refractive development is regulated by visual feedback. In particular, animal studies have shown that optically imposed myopic defocus slows axial elongation, that the effects of vision are dominated by local retinal mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 102 publications
3
94
0
5
Order By: Relevance
“…26 Wear of conventional spectacles does appear to contribute to this peripheral defocus, 27,28 which provided the impetus for the randomized trials of under-correction in preventing myopia progression as cited above. 14,15 The mechanism whereby spectacle wear (compared to nonwear) appears in fact to retard worsening of vision associated with progression of myopia is not well understood.…”
Section: Results From Itt Analysis In This Randomized Trialmentioning
confidence: 99%
“…26 Wear of conventional spectacles does appear to contribute to this peripheral defocus, 27,28 which provided the impetus for the randomized trials of under-correction in preventing myopia progression as cited above. 14,15 The mechanism whereby spectacle wear (compared to nonwear) appears in fact to retard worsening of vision associated with progression of myopia is not well understood.…”
Section: Results From Itt Analysis In This Randomized Trialmentioning
confidence: 99%
“…The emerging data from recent clinical trials show that optical strategies that take into account the peripheral retina and influence imagery over large part of the retina appear to produce larger reductions in myopia progression than those that do not. 59 More importantly these novel lens designs are producing clinically significant reductions in the progression of myopia in children.…”
Section: Discussionmentioning
confidence: 99%
“…54 Regardless, the pattern of results indicate that optical treatment strategies that take into account the optical state of the periphery are likely to be more successful than those that do not. 59 …”
Section: Peripheral Visual Signals Can Dominate Central Refractive Dementioning
confidence: 99%
“…The effect of undercorrection of myopia on myopia progression in school-aged children is still controversial [15]. Some studies [16][17][18][19][20] have reported that undercorrection retarded myopia progression compared to full correction, with differences of −0.05 D/year to −0.40 D/year.…”
Section: Introductionmentioning
confidence: 99%